The Covid-19 Pandemic and Meaning in Life - Attoe, Aribiah David; Chimakonam, Jonathan (Phronimon, 2021)
In the face of the Covid-19 pandemic, where death, sickness and suffering persist, there is some hint that there is nothing so special about the human race that particularly makes it immune to decimation. This is at odds with the general feeling that there is something significant, purposeful and/or meaningful about human life. Thus, the question that immediately comes to mind is whether the present pandemic and the negative situations it presents, destroy any hope of attaining meaning in life. In this article, we critically examine how the Covid-19 pandemic affects meaning in life. While it is not far-fetched to assume that the pandemic, suffering, isolation, economic hardship, and so forth disrupt humanity’s abilities at creating moments of meaning in life, it is our claim that it does not destroy it altogether, as many persons have found new ways of creating such moments, albeit small, through self-sacrifice/care, solidarity, and more. Finally, we conclude that in the face of this tragedy, what humanity can best hope for is the continuous creation of moments of meaning in life in order to reduce despair and sustain hope, however small. We expect that this article will foster future discussions about the impact of the Covid-19 pandemic on the question of meaningfulness.